Investigating Healthcare Educators' Interprofessional Socialisation Following an Interprofessional Simulation Facilitator Training Programme: A Mixed Methods Study - Dolan, Sara; Nowell, Lorelli; Moules, Nancy; Kaba, Alyshah; Brockway, Meredith (Journal of advanced nursing, 2025)
Interprofessional socialisation can contribute to collaborative patient care. Although there is research regarding interprofessional socialisation of healthcare students and frontline staff, there is limited literature regarding healthcare educators in practice settings. Our aim was to examine interprofessional socialisation of healthcare educators in the practice setting following an interprofessional simulation facilitator training programme. Explanatory sequential mixed methods study. Quantitative provincial simulation programme evaluation data from 2022 and 2023 (n = 87) were analysed and used to inform qualitative interviews (n = 17). Qualitative and quantitative data were integrated following independent analysis. There was a statistically significant increase in attitudes toward interprofessional socialisation following the simulation facilitator training programme. Qualitative findings revealed themes regarding interprofessional socialisation: (a) benefits gained through interprofessional socialisation, (b) interprofessional, uniprofessional or both, (c) facilitators to interprofessional socialisation, (d) barriers to interprofessional socialisation and (e) opportunities to strengthen interprofessional socialisation. Despite positive views of interprofessional socialisation, socialisation behaviours may not be consistent in a variety of contexts. Interprofessional education may increase interprofessional socialisation among educators. It is important to provide interprofessional socialisation opportunities for educators to promote more interprofessional education initiatives. The findings of this study provided insights into how to foster interprofessional socialisation in existing structures and how new pathways might be built to connect educators. This study is reported in congruence with the Journal Article Reporting Standards-Mixed Methods, Quantitative, and Qualitative Standards provided on the Equator Network. Members of the provincial simulation team were consulted regarding study design and data collection to optimise participation.